Associations between greenspace characteristics and population emotion perceptions in three dimensions - Cao, Zheng; Cao, Ye; Wu, Zhifeng (Frontiers in Environmental Science, 2023)
Mental disorders are considered to be the most significant threat to public health. Mitigation effects of urban green spaces have been widely documented. However, the conclusions reached have been inconsistent because of the representativeness of the original data. Thus, we measured the mental perception of urban green spaces using geospatial big data instead of field observation or questionnaire data. Street-view data were applied to calculate urban green space characteristics in three dimensions. The results showed that the positive mental perception percentage around the chosen urban parks increased as the buffer diameter decreased. The temporal variations of positive mental perceptions around the selected urban parks exhibited an obvious peak-trough shape. The spatial associations between the positive mental perception percentage and urban green space characteristics varied geographically. The spatial associations became less similar as the spatial buffer diameter decreased. At the same spatial-scale level, the green view played a dominant role in the spatial distribution of positive mental perceptions. The results indicated that shrinking the deviations of urban green space characteristics and increasing the mean and maximum values of urban green space characteristics will favor the improvement of public mental health. This study provides a reference for explaining ecological scientific questions using spatiotemporal big data; it also provides insights into the mechanisms underlying the relationship between ecological processes and public health.